Turkish hazel (Corylus colurna L.) in Hungary: A case study on its forestry potential - Ábri, T.; Magyar, L.; Rédei, K. (International Journal of Horticultural Science, 2026)
This study investigates the structure and growth of a 73-year-old Turkish hazel (Corylus colurna L.) plantation in Hungary. The stand had a tree density of 290 per ha, mean height of 18.2 m, quadratic mean diameter of 34.2 cm, and a basal area of 26.7 m² ha⁻¹. The slenderness ratio of 0.55 indicates moderate stability. Diameter distribution was normal (22–53 cm). Crown structure parameters showed moderate correlations with diameter (R² = 0.59 for crown diameter; R² = 0.53 for crown projection area), emphasizing the role of crown traits in yield modelling. An optimal planting density of 434 trees ha⁻¹ was estimated based on the average crown projection area (23 m2). Turkish hazel, with its drought resilience and valuable wood, is a promising species for afforestation in semi-arid climates. However, further research is needed on its management and genetic improvement to support wider application. This study can be considered gap-filling both in a Hungarian and, to some extent, an international context.